Design of the self-oscillating loop of the optically pumped cesium magnetometer. Issue 1 (February 2021) - Xue, Liyue; Dong, Haobin; Luo, Wang; Ge, Jian; Liu, Huan
Abstract: The self-oscillating loop is an important part of the optically pumped cesium magnetometer, and its working characteristics directly determine the accurate measurement of external magnetic field. The design of the self-oscillating loop has been discussed in this paper, including a signal conditioning circuit, a phase shifter and a frequency meter. It can be used to precisely improve the accuracy of resonance signal in a wide range of frequencies from 50 kHz to 350 kHz. The relative error of our system is less than 0.5×10 −6 and it has a good prospect in the optically pumped cesium magnetometer.